2018
DOI: 10.22201/fq.18708404e.2018.1.63680
|View full text |Cite
|
Sign up to set email alerts
|

Socio-scientific issues as contexts for relevant education and a case on tattooing in chemistry teaching

Abstract: <p>Context-based science education suggests that meaningful science teaching should be based on the lifeworld, society, or potential professional future of the pupils. But: Are all corresponding contexts for science education similarly good? This paper presents a curriculum model for using socio-scientific issues as contexts for science education in general and chemistry education in particular. It discusses the implications of this approach and presents an example on chemistry teaching about the issue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Given the foregoing issues, Stuckey et al (2013) have released the relevance model of science/chemistry education to make science learning relevant. Further, preliminary research papers on the relevance model have reported that socio-scientific issues (SSI) can be used to make science/chemistry learning more relevant (e.g., Eilks et al, 2018;Stuckey & Eilks, 2014;Zowada et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the foregoing issues, Stuckey et al (2013) have released the relevance model of science/chemistry education to make science learning relevant. Further, preliminary research papers on the relevance model have reported that socio-scientific issues (SSI) can be used to make science/chemistry learning more relevant (e.g., Eilks et al, 2018;Stuckey & Eilks, 2014;Zowada et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Because chemistry plays a milestone in addressing chemistry-focused SSI and finding alternative ways or solutions (Bertozzi et al, 2016;Seery, 2015), students are able to explore chemical problems using conceptual and procedural connections and judge social significance of chemistry on the community or daily life. For example, Eilks et al (2018) used some chemistry-focused SSI (e.g., musk fragrances in shower gels, low-fat and low-carb diets, doping in professional and leisure sports, bioplastics, Stevia controversy, natural cosmetics, and tattooing) to inform students about responsible citizenship and scientific/chemical literacy. Handling SSI within school chemistry necessitates to learn chemistry concepts and perceive chemistry-related disciplines (e.g., biology, physics, earth sciences, environmental sciences).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using educational topics adopted from issues of daily life and society, such as health, food, and fuel (e.g., Broman and Parchmann, 2014), enables students to recognize the importance of chemistry in understanding scientific phenomena and technological problems (Gilbert, 2006). Furthermore, socioscientific issues (SSIs) were reported as a potential topic to make chemistry learning relevant (e.g., Eilks et al, 2018;Zowada et al, 2020) since it helped students to connect the scientific concepts and social problems in their daily lives (Capkinoglu et al, 2019). Previous studies showed that bringing SSI in science learning improved students' decision making (Rizal et al, 2017;Christenson et al, 2014, and students' awareness toward environmental and daily problems (e.g., Juntunen and Aksela, 2013;Korolija et al, 2015;Drury et al, 2016;Shamuganathan and Karpudewan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, exploring students' SHOM via SSIs supports their ability in making an appropriate decision toward SSIs (i.e., road salting, tattooing, mass vaccination, climate change, fossil fuels, use of lead, and acid rain) within considering any facts and evidence in promoting chemical literacy (e.g., Cigdemoglu and Geban, 2015;Blonder et al, 2016;Çalik and Cobern, 2017;Eilks et al, 2018;Zowada et al, 2018). Chemical literacy ability helps students become more critical, analytical, and creative in ways that support the development of 21st-century skills.…”
Section: Introductionmentioning
confidence: 99%